Toward Informed Regulatory Conversations and Improved Regulatory Regime in the Philippines: Logistics Sector and Trade Facilitation - Gilberto M. Llanto; Adoracion M. Navarro; Keith C. Detros; Ma. Kristina P. Ortiz (Philippine Institute for Development Studies (PIDS), 2013)
This study articulates the results of the research team's conversations with regulators and desk review of policies in the sectors affecting logistics and trade facilitation in the Philippines. The study covers air transport, land transport, maritime transport, logistics services, and customs services. Successes in regulatory reforms as well as the remaining restrictions to better logistics and trade facilitation surfaced from the conversations with regulators and the analysis of existing rules and regulations. Many of the remaining restrictions need to be addressed through amendments to existing laws and even enactment of new laws. This is the case in the following restrictions: limit on foreign equity participation, moving international government cargoes only through flag carriers, cabotage restriction, and the port regulator acting as an operator. Other remaining restrictions can be addressed through investments, which is the case in capacity-constrained airports and congested Metro Manila roads, and through improvements in operations, which is the case in customs administration.
Keywords: 330; maritime transport; customs; regulation; trade facilitation; logistics; ASEAN Economic Community (AEC); air transport; land transport